RUSSIAN UNIVERSITIES IN GLOBAL RATINGS - Ildar U. Zul'karnay; Guzel R. Islakaeva (Высшее образование в России, 2016)
This paper conducts comparative analysis of Russian universities' positions in international and Russian rating systems. Particular attention is paid to universities that have obtained special statuses: "Federal University", "National Research University" and also to universities that participate in federal project "5-100". This project targets the Russian